Consumption patterns of grains/cereals, vegetables and fruits and its association with glycemic control among patients with type 2 diabetes mellitus; A cross sectional study - Mariam John Munyogwa; Festo Phineas Maregesi (Clinical Nutrition Open Science)
Summary: Background & aims: The world is experiencing steady increasing in both number of cases and prevalence of diabetes with urban settings being more affected areas. Good adherence to dietary management is a key non-pharmacological management for effective management of blood glucose for people living with type 2 diabetes. For effective glycemic control, people with diabetes are recommended to eat less carbohydrates (quarter plate size), more fruits and vegetables (half plate size) and more lean protein (quarter plate size). This study aims to assess the consumption patterns of grains/cereals, vegetable and fruits and its association with glycemic control among people living with diabetes. Materials & Methods: The study design was a cross sectional among outpatients attending routine diabetic clinics. Structured questionnaire was used to collect information from the patient through face to face interview. Demographic information, dietary history and selected medical history were collected from patients. Data analysis was done by running the frequencies, percentages, chi-square test and logistics regression at 95% confidence interval. Results: About 109 (33.1%) of respondents were aged less than 40 years. One hundred and fifty-two respondents had been living with diabetes for less than past 5 years 152 (46.2%). More than 80% of the respondents had uncontrolled glycemic. Daily consumption patterns of grains/cereals food were (90.0%), vegetables (97.3%) and fruits (33.4%). Plate portion size consumed were; ≤¼ for grains/cereals (50.5%), ≥¼ for vegetables (96.4%) and ≥¼ for fruits (30.7%). The most types of food consumed were legumes (85.1%), whole grains/cereals (57.1%), leafy green vegetables (70.2%) and low GI fruits (59.9%). The odds of having hyperglycaemia were; increasing with increase in portion size of grains/cereals food (ref: one fifth; one quarter, AOR = 10.22; one third, AOR = 47.19; one half or more, AOR = 42.91); increasing with consumption of high GI fruits (AOR = 2.40) and decreasing with increase in portion size of fruits (AOR = 3.13). Conclusion: Grains/cereals, vegetables and fruits consumption pattern among patient with type 2 diabetes need to improve to achieve optimal blood glucose. Reducing staples portion sizes (grains/cereals), increases portion size for mixed fruits, eating whole grains/cereals and choosing of low GI fruits may help to curb the severity of hyperglycemia among patients with T2DM.